Dent Disease Type 2 as a Cause of Focal Segmental Glomerulosclerosis in a 6-Year-Old Boy: A Case Report - Bezdíčka, Martin; Langer, Jan; Háček, Jaromír; Zieg, Jakub (Frontiers in Pediatrics, 2020)
Dent disease is an X-linked recessive renal tubular disorder characterized by proximal tubule dysfunction. Typical features include low molecular weight proteinuria, hypercalciuria, nephrocalcinosis, nephrolithiasis, rickets and chronic renal failure. We present a case of a 6-year-old boy with nephrotic proteinuria without hypoalbuminemia or edema. His renal biopsy revealed focal segmental glomerulosclerosis (FSGS), some of the glomeruli were globally sclerotic. Hypercalciuria was present intermittently and urine protein electrophoresis showed low molecular weight protein fraction of 50%. The next generation sequencing identified pathogenic variant in OCRL gene causing Dent disease type 2. We report an uncommon histologic finding of FSGS in Dent disease type 2 and highlight the importance of protein content examination and genetic analysis for the proper diagnosis in these complicated cases.